Magnetic-Field-Orientation Dependent Magnetoelectric Effect in FeBSiC/PZT/FeBSiC Composites - Jun-Xian Ye; Jia-Mian Hu; Zhan Shi; Zheng Li; Yang Shen; Jing Ma; C. W. Nan (Advances in Materials Science and Engineering)
We investigate the magnetic-field-orientation dependent magnetoelectric (ME) effect in the FeBSiC/Pb(Zr,Ti)O3(PZT)/FeBSiC laminates. It is shown that, by only using the bias-magnetic-field dependent ME response measured with the magnetic-field parallel to the surface plane of PZT slab, the magnetic-field-orientation dependent ME coefficient upon magnetic-fields of various amplitudes can be obtained via computer simulations. The simulation results match well the experimental measurements, demonstrating the applicability of the ME laminates-based sensors in detecting magnetic-fields with uncertain amplitudes and/or orientations in environment.